Corporate Societal Marketing and the Process of Building Corporate Brand Equity: The Case of Malayala Manorama - Saji K.B. V. Mukundadas (International Marketing Conference on Marketing & Society, 8-10 April, 2007, IIMK, 2007)
Building corporate brand equity for one's own is considered as one of the most important governance responsibilities by most of the Indian companies today. This paper is an attempt by the authors to identify the factors that drive the process of corporate brand equity building up via the societal marketing route. For the exploration purpose, it has been decided to use the case study method. To start with, the authors attempted to capture and document an interesting initiative by the Malayala Manorama group of publications (referred to hereafter as Manorama), the largest newspaper network (in terms of reach and readership) operating from the South Indian state of Kerala. The present paper reports the preliminary outcomes of this study.